2019
DOI: 10.1111/cns.13124
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment of hyperbaric oxygen treatment mitigates inflammatory response via mitochondria transfer

Abstract: Summary Aims Hyperbaric oxygen therapy (HBOT) has been widely used as postinjury treatment; however, we investigate its ability to mitigate potential damage as a preconditioning option. Here, we tested the hypothesis that HBOT preconditioning mitigates cell death in primary rat neuronal cells (PRNCs) through the transfer of mitochondria from astrocytes. Methods Primary rat neuronal cells were subjected to a 90‐minute HBOT treatment at 2.5 absolute atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…However, the results of some studies have suggested that extracellular mitochondria play unfavorable roles. Mitochondria from traumatized brain tissues were able to stimulate platelets and promote their procoagulant activity, contributing to TBI-induced coagulopathy and in ammation [76]. Furthermore, in our present study, we also surprisingly observed that the protective effects of isolated mitochondria were oxygen-dependent, where the treatment of isolated mitochondria could cause detrimental effects under hypoxic conditions and promote protective effects in a normal oxygen environment.…”
Section: Discussionsupporting
confidence: 72%
“…However, the results of some studies have suggested that extracellular mitochondria play unfavorable roles. Mitochondria from traumatized brain tissues were able to stimulate platelets and promote their procoagulant activity, contributing to TBI-induced coagulopathy and in ammation [76]. Furthermore, in our present study, we also surprisingly observed that the protective effects of isolated mitochondria were oxygen-dependent, where the treatment of isolated mitochondria could cause detrimental effects under hypoxic conditions and promote protective effects in a normal oxygen environment.…”
Section: Discussionsupporting
confidence: 72%
“…Oxygenation improves energy metabolism in the border zones of focal cerebral ischemia represented by significant reduction of areas with tissue acidosis and areas with ATP depletion (Sun, Marti, & Veltkamp, 2008;Sun, Strelow, Mies, & Veltkamp, 2011).HBOT can also decrease the post ischemic inflammatory response by reducing blood-brain-barrier damage (Veltkamp et al, 2005), inflammatory cytokines release (Yu, Xue, Liang, Zhang, & Zhang, 2015) and suppresses the aggravated response of astrocytes and microgliosis (Gunther et al, 2005). Recently, it was shown HBOT mitigates the inflammatory response of the neuronal cells through the transfer of mitochondria from astrocytes (Lippert & Borlongan, 2019). HBOT reduces apoptosis which enables to preserve more brain tissues and promote neurologic functional recovery (Yin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke and TBI, two principal forms of ABI, pose a significant health and economic burden globally, and limited treatment options necessitate a novel therapeutic strategy to attenuate disease progression. [88][89][90][91] Primary cell death directly results from stroke or TBI, and the extent of this, brain damage is categorized as either focal or diffuse. Along with the influence of patient age, central and peripheral sources of immune cells prominently contribute to secondary neurodegeneration during both the acute and chronic phases following stroke and TBI.…”
Section: Con Clus Ionmentioning
confidence: 99%